The Role of Digital Economy in Shaping Economic Growth in Belt and Road Initiative Countries - Robeena Bibi; Sumaira (Journal of Environmental Science and Economics, 2025)
Global trade dynamics have been re-shaped by the rapid development of digital technologies, but the role played by these changes in economic growth in countries is poorly understood. The study considers 149 developing countries that are engaged in the Belt and Road Initiative to explore the relationship between the digital economy, international trade and economic growth. Using data between the years 2000 and 2024 and dynamic panel models, results demonstrate that international trade helps the growth of economic growth significantly while the overall digital economy has a negative impact, which may indicate existing digital infrastructure is a barrier. The interplay between trade and the digital economy drives the need for policies that unite both trade and the digital initiative approach. The study suggests that digital capabilities must be improved in the sample countries for the maximum trade benefits to be generated and for growth to be stimulated. Policymakers should look into improving digital infrastructure and digital literacy in order to make international trade more efficient and facilitate higher economic growth.